Discursive Decoys: The Legitimation of Homophobia and Transphobia, Educational Neutrality, and Teacher Deprofessionalization in Mainstream Media’s Coverage of the “Parental Rights” Movement in Manitoba - Moore, Shannon; Lopuck, Kevin (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2025)
In the 2023 provincial election in Manitoba, the Progressive Conservative Party (PC) committed to enhancing “parental rights” in education if elected for a second term. This article examines the way the PCs’ campaign materials, surrounding media coverage, and responses from provincial public education partners legitimized the underlying discourses of the “parental rights” movement. This movement endorses the erasure and harm of 2SLGBTQIA+ students and community members, disregards and undermines children’s rights, and privileges the perspectives of particular parents. Using critical discourse analysis, we outline the way that homophobic and transphobic discourses are legitimized through the coverage of this campaign. We also outline the ways that neutrality is weaponized in order to secure heteronormativity in schools. Moreover, we reveal the ways that teachers are villainized (criminalized) in order to advance “parental rights” claims. By putting discursive tactics on display, this article reveals the way that power is operationalized and secured.